2008
DOI: 10.1016/j.anbehav.2008.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Does common spatial origin promote the auditory grouping of temporally separated signal elements in grey treefrogs?

Abstract: ‘Sequential integration’ represents a form of auditory grouping in which temporally separated sounds produced by the same source are perceptually bound together over time into a coherent ‘auditory stream’. In humans, sequential integration plays important roles in music and speech perception. In this study of the grey treefrog (Hyla chrysoscelis), we took advantage of female selectivity for advertisement calls with conspecific pulse rates to investigate common spatial location as a cue for sequential integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 57 publications
2
32
1
Order By: Relevance
“…Across all five tests, the mean response latencies ranged between 65s and 91s, and the fastest response latencies ranged between 30s and 38s; these latencies are fairly typical for this species (e.g. Bee and Riemersma, 2008). Together, these results suggest the following.…”
Section: Experiments 2: Validation Of Sam Tones As Attractive Signalssupporting
confidence: 58%
“…Across all five tests, the mean response latencies ranged between 65s and 91s, and the fastest response latencies ranged between 30s and 38s; these latencies are fairly typical for this species (e.g. Bee and Riemersma, 2008). Together, these results suggest the following.…”
Section: Experiments 2: Validation Of Sam Tones As Attractive Signalssupporting
confidence: 58%
“…Several studies have now demonstrated spatial release from masking in Cope’s gray treefrogs, and have shown that it reduces response latencies and increases response probabilities in phonotaxis tests (Bee 2007b; Ward et al 2013a), reduces signal recognition thresholds (Nityananda and Bee 2012), and improves temporal pattern discrimination in the context of species recognition (Bee 2008; Ward et al 2013a). Studies of auditory grouping and auditory stream segregation in this species indicate spatial cues might be relatively more important for perceptually binding simultaneous signal components, such as the harmonics in the bimodal frequency spectrum of calls, than for binding sequentially produced signal components, such as pulses (Bee and Riemersma 2008; Bee 2010). While the present study represents an important first step, there is a clear need for additional investigations of the biomechanics and neurophysiology of spatial hearing in Cope’s gray treefrogs.…”
Section: Discussionmentioning
confidence: 98%
“…Spatial hearing is also important in other perceptual and cognitive tasks not directly related to sound source localization. Three such likely tasks involve auditory grouping (Schwartz and Gerhardt 1995; Farris et al 2002, 2005; Bee and Riemersma 2008; Bee 2010; Farris and Ryan 2011), spatial release from masking (Schwartz and Gerhardt 1989; Bee 2007b, 2008; Nityananda and Bee 2012; Ward et al 2013a), and cross-modal sensory integration (Narins et al 2005; Taylor et al 2011). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frogs appear to group temporally separated components of their signals over wide angles of spatial separation (e.g., Farris et al, 2002, 2005; Farris and Ryan, 2011; Gerhardt et al, 2000a). Thus far, two studies have tested the hypothesis that spatial proximity promotes sequential integration in gray treefrogs ( H. chrysoscelis and H. versicolor ) (Bee and Riemersma, 2008; Schwartz and Gerhardt, 1995). Both studies used interleaved sequences of pulses to take advantage of the natural selectivity that females have for conspecific pulse rates, which are about twice as fast in H. chrysoscelis (35–50 pulses/s) compared with H. versicolor (19–24 pulses/s) (Gerhardt, 2001).…”
Section: Auditory Scene Analysis In Hylamentioning
confidence: 99%